An Analysis Of The Recording And Assessment Methods Of Inventory At Carnova Variasi Kota Bengkulu - Lestari, Putri Ayu Endah; Susanti , Neri; Astuty , Kamelia (Universitas Dehasen Bengkulu, 2024)
A better inventory system can increase profit, while a less efficient system can erode profit and make a business less competitive. The main benefit of inventory formation is to protect the company from unforeseen events and disruptions in business. The aim of this research is to analyze the recording and assessment methods of inventory at Carnova Variasi Kota Bengkulu. The recording and assessment methods of inventory, specifically for car seat covers, rice noodle carpets, and android head units at Carnova Variasi Kota Bengkulu over a 12-month period from May 2023 to April 2024, will be compared with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) no.9 of 2018. Data collection was done through documentation and research analysis using comparative descriptive analysis. The results were in line with the recording method recommended by SAK EMKM regarding inventory. This is because Carnova Variasi Kota Bengkulu recorded inventory at the time of purchase and sale into detailed purchase and sales reports leading to a perpetual recording method system. Additionally, Carnova Variasi Kota Bengkulu used stock cards as a means of controlling its inventory. However, there are still some discrepancies such as not journalizing at the time of purchase and sale. The inventory assessment system implemented by Carnova Variasi Kota Bengkulu is the weighted average valuation method, which complies with SAK EMKM regarding inventory. This can be seen in the determination of the cost of goods sold taken from the average inventory price by dividing the total purchase price by the existing inventory. However, the inconsistency lies in the fact that Carnova Variasi Kota Bengkulu did not prepare financial statements, resulting in the absence of inventory presentation in the balance sheet.